Diversity and proximate composition of herbaceous components of old oyo national park, nigeria in relation to wildlife conservation (2009)
The diversity of wildlife in Parks depends on availability and distribution of flora feeding resources. Abundance and proximate relationships between wild plants and wildlife may determine conservation potentials of a Park. The composition and diversity of species in three wetlands (Ibuya, Ipade-Aya and Ajalcu) in Old Oyo National Park, Nigeria were studied in dry (February-March) and wet (September- October) seasons of 2004-2006. Herbaceous flora of the three wetlands were systematically assessed using 5000 m2 plots on which two 100 m diagonal transects were superimposed to enumerate all low-growing plants that rooted within thirty randomly selected 1 m2 quadrats. Four most abundant plant species in two families were selected for proximate analyses. Three topsoil samples of each site were randomly collected and analysed for physicochemical properties. Hyparrhenia involucrata Stapf. and Andropogon tectorum Schumach were the most abundant herbs in the wetlands. Ipade-Aya had the highest Shannon-Weiner (H1) and evenness (J) values of 1.6 and 0.7 respectively. Ibuya had H'=1.0 and J=0.5; while Ajalcu had H'=1.0 and J=0.5. The protein contents of the forage grasses significantly (P<0.05) ranked in the order: Andropogon tectorum > Andropogon gay anus Kunth > Hyparrhenia involucrata > Hyparrhenia rufa (Nees) Stapf. Soils of the wetlands were mostly similar, except Ajalcu which was sandy loam. Fauna populations at the three sites were low. The highest detected faunal populations were nine at Ibuya, and three each at Ipade-Aya and Ajaku. Available nutritious grasses may not continue to sustain wildlife populations. Further research should consider increasing forage for faunal conservation.